1921 Wis. Sess. Laws 870, ch. 530, § 1. - (:unkn) unknown (General Publisher, 1921)
No person shall hunt game with any means other than the use of a gun held at arm’s length and discharged from the shoulder; or place, spread or set any net, pitfall, spring gun, pivot gun, swivel gun, or other similar contrivance for the purpose of catching, or which might catch, take or ensnare game . . . and no person shall carry with him in any automobile any gun or rifle unless the same is unloaded, and knocked down or unloaded and inclosed within a carrying case[.]
--
Keywords: HUNTING REGULATION